Analysis of Internal Communication in the Management of a Cuban Hotel Facility - Góngora Ruíz, Mónica Lizt; Varona Silva, Francisco Javier; Cruz Aguilera, Nolberto (Espergesia, 2025)
Internal communication represents a strategic asset in hotel organizational management. However, its institutionalization remains an unresolved challenge in many Cuban entities. The objective of this study was to comprehensively diagnose the state of internal communication at the Club Amigo Atlántico Guardalavaca Hotel, aiming to identify its structural weaknesses, human potential, and propose action lines aligned with a strategic management approach. Methodologically, this was a descriptive study with a mixed-methods design, applied to a stratified probabilistic sample of 169 employees. Techniques included document analysis, non-participant observation, semi-structured interviews, a communication review test, and surveys validated by five subject-matter experts. The instrument encompassed indicators such as flows, channels, functions, structures, organizational culture, and climate. Key findings revealed a strong preference for oral and face-to-face channels, such as morning briefings (63.9%), meetings (62.7%), and union assemblies (60.9%). Professionalism (88.2%), responsibility (82.4%), and sense of belonging (79.9%) emerged as dominant values. The absence of a formal communication advisory unit and the omission of communication processes from the organizational process map were also identified. It was concluded that internal communication is currently managed through a fragmented, top-down approach. Institutionalizing communication as a strategic axis is essential to build a participatory, resilient, and goal-oriented organizational culture; thus, a strategic restructuring that integrates culture, leadership, and communication is proposed.